Strengthen sustainability – transformations for climate protection through regional planningAbstract - Mölders, Tanja; Doyé , Laura; Gailing, Ludger (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
The climate crisis is one of the greatest challenges of the Anthropocene. The goal of Paris-compatible development (climate warming to 1.5°C or well below 2°C) therefore also addresses spatial planning. However, although sustainable spatial development is enshrined as a guiding principle of spatial planning and future and target orientation, action preparation and a systematic approach combine spatial planning and climate protection, the potential of overall spatial planning has rarely been utilised in shaping the transformation towards Paris-compatible development. Against this background, this paper analyses the relationship between spatial planning and spatial sustainability transformations using the example of climate protection. The guiding research question is how spatial planning with its paradigms, concepts and instruments can be located in the spatial transformation debate. In an empirical part, the results of a Delphi study are presented, in which the contributions of regional planning to climate protection are discussed. The results show that formal planning is certainly capable of contributing to sustainability transformations. However, in order to be able to consistently orientate its potentially powerful design options towards strong sustainability, regional planning itself requires a transformation in some areas.
Keywords: Formal planning; Regional planning; Strong sustainability; Spatial sustainability transformations; Climate protection